Milk Collection Systems and Profitability of Commercial Dairies in Bikaner (Rajasthan) - Chand, Khem; Singh, Kulwant; Kumar, Shalander (Annals of Arid Zone, 2016)
The overall net return and family labor income from a liter of milk were Rs. ] .93 and 2.76, respectively. The milk producers were selling the milk directly to consumers. sweet manufacturing units and organized dairy plants. etc. The auctioning and contractual procurement of milk is the special feature of milk marketing in Bikaner. The contract ensures a remunerative floor price to milk producers. The study has revealed the increased profitability of milk production. which is reflected through increase in the number of dairy herds by about 30% in a period of three years